Pattern of Presentation of Chronic Venous Insufficiency in CVI Clinic of Chittagong Medical College Hospital - Salim, Md; Hossain, GM Zakir; Rahman, Mahmudur; Alam, Md Monirul; Khan, Muallem Al Farukh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Chronic Venous Insufficiency (CVI) is a common but often ignored problem in primary health care, sign and symptoms may ranges from mild leg heaviness or aching, dilated or unsightly veins, or troublesome odema to fibroses subcutaneous panniculitis associated with recurrent cellulitis and chronic ulceration. Methods: The prospective observational study was carried out Depaertment of Surgery, Chittagong Medical College Hospital, Chittagong. The primary purpose of the present study was to evaluate the impact of the diagnostic approach on patient of chronic venous insufficiency, varicose vein to difference primary and secondary venous insufficiency. Results: Most common sign flebedema found in 56 (65.12%) patients was followed by dermo-hypodermatitis in 15(17.44) patients, stasis eczema in 09(10.47) patients and thrombophlebitis in 06(6.98) patients. Most frequent lower leg symptoms are heaviness 82 (95.35%) & the lowest is throbbing 55(63.95%). The others are according to order of Frequency cramps 66 (70.0%) Itching 63 (73.26%) Burning 61(70.93%) Tiredness 69 (80.23%) Restless leg 71 (82.55%) Pain aching 76 (88.37%). CVI (Chronic Venous Insufficiency) studied 04 (4.65%) were in C1, 54(62.79%) were in C2, 03(3.49%) were in C3, 11(12.79%) were in C4, 6 (6.98%) were in C5 and 8(9.30%) were in C6 according to clinical CEAP classification. Conclusion: Majority of patients presented with the complains of heaviness of leg and unexplained leg swelling, sex predilection is almost same for male and female but advanced stages are more common in male patients. Increasing age is associated with more advanced stage of the disease. Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 51-55